Goals and activities proposed by countries in seven regions of the world toward prevention of unsafe abortion - Mirembe, Florence; Karanja, Joseph; Osman Hassan, Ezzeldin; Faúndes, Anibal (International Journal of Gynecology & Obstetrics, 2010)
This article describes the goals and activities included in the national plans of action for the prevention of unsafe abortion. With broad variability, all were in line with the initiative's purpose of contributing to reduce the number of women who have unplanned pregnancies and induced abortions, as well as the maternal mortality and morbidity associated with unsafe abortion. The interventions proposed can be classified in 5 groups: (1) to work toward better national policies through obtaining and disseminating accurate evidence based data on abortion and to sensitize policy makers and health professionals on issues pertaining to unsafe abortion; (2) to reduce the number of unplanned/unwanted pregnancies by increasing the use of modern contraceptive methods, introducing or improving sex education, and improving adolescent-friendly reproductive health services; (3) to make induced abortion safer by making adequate abortion services available, within the full extent of the national laws, and promoting access to safe abortion; (4) to improve post abortion care, including post abortion contraception; and (5) to reduce the need to resort to abortion by working on facilitating the process of adoption. The proportions of plans that include each of these interventions are described, as well as some regional differences.
Keywords: Interventions; Plans of action; Prevention; Regional variability; Unsafe abortion